Pengaruh Pemberian Aromaterapi Lavender Terhadap Frekuensi Mual Muntah Pada Ibu Hiperemesis Gravidarum Trimester 1 Wanita di Ruang RSIA Sitti Khadidjah A Isyiah Obligent Polygorontalo City - Harismayanti Harismayanti; Ani Retni; Nurjana Dilihama (Universitas Katolik Widya Karya Malang, 2023)
Introduction: A woman experiences pregnancy, which lasts from the moment of conception (fertilization) until the baby is born. This process produces physical, psychological, environmental, socio-cultural, and economic changes that affect the body, mind, and society. Pregnant women often experience nausea and vomiting (Emesis Gravidarum), especially in the first trimester of pregnancy.Objective : To determine the effect of giving lavender aromatherapy in reducing the frequency of nausea and vomiting before and after being given lavender aromatherapy to pregnant women in the first trimester. Research Method: This pre-experimental research design used a responsive pre-post test because it only involved one group of subjects. The subject's body was detected before the intervention was carried out, then detected again after the intervention was carried out. The subjects used in this study were pregnant women who experienced hyperemesis gravidarum in the first trimester of pregnancy. Results: It is known that Clients 1 and 2 experience nausea and vomiting more often than four times a day before receiving lavender aromatherapy. For Client 1, the frequency of nausea and vomiting was found to decrease after receiving lavender aromatherapy for three consecutive days, and the client did not experience nausea or vomiting at all. For Client 2 there was no change in giving lavender aromatherapy because the client continued to experience nausea and vomiting with a frequency of about 2 times per day. Conclusion: the overall evaluation results showed that one of the clients used non-pharmacological techniques and received lavender aromatherapy which caused a decrease in nausea, while the other clients who received lavender aromatherapy continued to experience nausea and vomiting. about twice a day vomiting.